Pengaruh Kompensasi terhadap Kinerja Pegawai pada Distrik Bikar Kabupaten Tambrauw - Aifamas, Alex; Andriani Renouw, Ade; Sinay, Philipus (CV. Creative Tugu Pena, 2022)
This study aims to analyze the Effect of Compensation on Employee Performance in Bikar District, Tambrauw Regency. The data analysis method used is quantitative descriptive analysis. significant test through (t-test), using simple linear regression and coefficient of determination (R2). The population in this study were all employees in the Bikar District, TambrauwRegency. the sample amounted to 34 respondents. Primary data were obtained through interviews, questionnaires and documentation studies. From the results of data processing simple linear regression analysis using the SPSS for windows version 25 program, the regression equation Y = 6.432 + 0.762X, the regression coefficient value of 0.762 means that every time there is a change and an addition of one percent in the compensation variable, the employee performance variable will increase by 0.762 if the compensation variable is zero, then the employee's performance has a value of 6.432. In the coefficient of determination test obtained R square 54.6%. it means that compensation has an effect on employee performance by 54.6%. while the remaining 45.4% is influenced by other factors not analyzed in this study. Theresultsofthet-test,wheretcount6.201>fromttable1.6939, it can be said that the compensation variable has a positive and significant effect on employee performance. Keywords: Compensation Employee, Employee Performance, Compensation on Employee